2020
DOI: 10.1002/fam.2928
|View full text |Cite
|
Sign up to set email alerts
|

Thermal protective performance of firefighting protective clothing incorporated with phase change material in fire environments

Abstract: Summary Phase change materials (PCMs) can optimize the thermal properties of fabric. Twelve kinds of microencapsulated phase change materials were selected, including four different phase change temperatures and three different content gradients. Twelve kinds of PCM‐coated fabrics were prepared by dry coating, and their basic physical properties were tested. The PCM‐coated fabric was added to the thermal protective fabric system as a comfortable layer. The thermal protective performance of the fabric system un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The sandwich fibrous PEG encapsulation was not the best one while it was possible to have higher overall enthalpy values by using proper protection layer with lower areal density. In addition, the PEG loading amount in our research work was as high as 45 wt %, which was comparable with other PCM fabrics [14,31,[45][46][47][48] (Table S17 in Supporting Information). As shown in Figure 6.…”
Section: Discussionsupporting
confidence: 82%
“…The sandwich fibrous PEG encapsulation was not the best one while it was possible to have higher overall enthalpy values by using proper protection layer with lower areal density. In addition, the PEG loading amount in our research work was as high as 45 wt %, which was comparable with other PCM fabrics [14,31,[45][46][47][48] (Table S17 in Supporting Information). As shown in Figure 6.…”
Section: Discussionsupporting
confidence: 82%
“…The results showed that the specimens containing PCMs had an excellent heat insulation effect as the skin temperature did not reach 10 C after cooling for 800 s, while those of the raw sample were within 400 s. Moreover, the gentle cooling rate of the former provided a more comfortable body feeling and had great prospects in the textile industry. Wang et al 98 numerically studied the combined heating conditions with convection and radiation in the fire scene by thermal protective clothing to evaluate the thermal performance of firefighting protective fabrics combined with PCM. The fabric was explored at the heat flux of 8.5 kW/m 2 for 300 s, and the seconddegree burn times for the fabrics incorporated with PCM were significantly higher than those without PCM, which was extended by 36.6-57.9 s according to the content of PCM.…”
Section: Thermal Management Of Smart Textiles and Thermoregulating Co...mentioning
confidence: 99%
“…Wang et al. 98 numerically studied the combined heating conditions with convection and radiation in the fire scene by thermal protective clothing to evaluate the thermal performance of firefighting protective fabrics combined with PCM. The fabric was explored at the heat flux of 8.5 kW/m 2 for 300 s, and the second-degree burn times for the fabrics incorporated with PCM were significantly higher than those without PCM, which was extended by 36.6–57.9 s according to the content of PCM.…”
Section: Thermal Management Of Smart Textiles and Thermoregulating Co...mentioning
confidence: 99%
“…Flame-Resistant Cotton [8], Carbon Fibre [9], FR Rayon fibres [10] are used by researchers to see their fire protective performance. Among all these fibres, Nomex IIIA comprises inherent properties of flame retardancy from its molecular structure [11]. Moreover, it has excellent protection capabilities against flash fires, and it can withstand its basic fire-retardant properties even after multiple washes.…”
Section: Introductionmentioning
confidence: 99%